Inokulmmängdens betydelse för utveckling av vetets stråbasröta orsakad Fusarium graminearum : utvärdering av ett biotest - Bertholtz, Erik (SLU/Dept. of Forest Mycology and Plant Pathology, 2013)
Fusarium graminearum is one of the most important pathogens on cereals and causes major crop losses around the world. The most cultivated cereal in Sweden is winter wheat. F. graminearum produces both sexual and asexual spores for dispersal. Multiple factors affect the production of these spores. Fusarium foot rot caused by Fusarium species is a disease of economical importance which can give crop yield losses between 35 % up to 61 %. In this trial a bioassay has been evaluated for the relation between dose and disease development by fusarium foot rot caused by F. graminearum. Disease index indicated a distinct trend with increasing symptom development with increasing conidia concentration while the dry weight matter result did not indicate a similar distinct trend. The bioassay gives a relatively quick result and is easy to execute. For a clearer result, more plants per concentration group should be used and a blind test should be used during the reading of symptoms.